1,2-Redox Transpositions of Tertiary Amides - Shennan, Benjamin D. A.; Sánchez-Alonso, Sergio; Rossini, Gabriele; Dixon, Darren J. (Journal of the American Chemical Society, 2023)
Reactions capable of transposing the oxidation levels of adjacent carbon atoms enable rapid and fundamental alteration of a molecule’s reactivity. Herein, we report the 1,2-transposition of the carbon atom oxidation level in cyclic and acyclic tertiary amides, resulting in the one-pot synthesis of 1,2- and 1,3-oxygenated tertiary amines. This oxidation level transfer was facilitated by the careful orchestration of an iridium-catalyzed reduction with the functionalization of transiently formed enamine intermediates. A novel 1,2-carbonyl transposition is described, and the breadth of this redox transposition strategy has been further explored by the development of aminoalcohol and enaminone syntheses. The diverse β-functionalized amine products were shown to be multifaceted and valuable synthetic intermediates, accessing challenging biologically relevant motifs.